A follow-up study of occupational styrene exposure and risk of autoimmune rheumatic diseases. (17th December 2019) - Hjuler Boudigaard, Signe; Stokholm, Zara Ann; Vestergaard, Jesper Medom; Mohr, Mette Skovgaard; Søndergaard, Klaus; Torén, Kjell; Schlünssen, Vivi; Kolstad, Henrik A
Abstract : Objectives: Increased risk has been suggested for autoimmune rheumatic diseases following solvent exposure. The evidence for specific solvents is limited, and little is known about exposure–response relations. Styrene is an aromatic, organic solvent and the objective of this study was to analyse the association between occupational styrene exposure and autoimmune rheumatic diseases in men and women. Methods: We followed 72 212 styrene-exposed workers of the Danish reinforced plastics industry from 1979 to 2012. We modelled full work history of styrene exposure from employment history, survey data and historical styrene exposure measurements. We identified cases in the national patient registry and investigated gender-specific exposure–response relations by cumulative styrene exposure for different exposure time windows adjusting for age, calendar year and educational level. Results: During 1 515 126 person-years of follow-up, we identified 718 cases of an autoimmune rheumatic disease, of which 73% were rheumatoid arthritis. When adjusting for potential confounders and comparing the highest with the lowest styrene exposure tertile, we observed a statistically non-significantly increased risk of systemic sclerosis among women (incidence rate ratio (IRR)=2.50; 95% CI 0.50 to 12.50) and men (IRR=1.86; 95 % CI 0.50 to 7.00), based on 9 and 22 cases, respectively. Results were inconsistent for the other autoimmune rheumatic diseases examined. Conclusion: This study suggests an association between occupational styrene exposure and systemic sclerosis in men as well as in women but based on few cases. This is a new finding and has to be replicated before conclusions can be drawn.